Branding Higher Education Institutions: What It Takes to be Branded - Amzat, Ismail Hussein (SPRINGER, 2016)
Over a long period of time, the word ‘brand’ has been used in business, marketing and advertising to distinguish the product of one unique seller from another. Today, we are living in a world of ‘customerisation’ in which customers opt for a product based on their desirability and according to their favourability and loyalty to a particular product, due, perhaps, to the unrivalled quality of the brand. Given this scenario, higher institutions share similarities with business products, as the core business and product of an educational institution are teaching and learning. Hence, this chapter explains the importance of branding in higher education institutions (HEIs). It elucidates what it takes to be branded by providing some principles in creating a brand and the various steps towards branding, as well as proposes a model for the branding of higher education institutions.